What does the brain tell us about abstract art? - Aviv, Vered (Frontiers in Human Neuroscience, 2014)
In this essay I focus on the question of why we are attracted to abstract art (or, perhaps more accurately, non-representational art). After elaborating on the processing of visual art in general and abstract art in particular, I discuss recent data from neuroscience and behavioral studies related to abstract art. I conclude with several speculations concerning our apparent appeal to this particular type of art. In particular, I claim that abstract art frees our brain from the dominance of reality, enabling it to flow within its inner states, create new emotional and cognitive associations, and activate brain-states that are otherwise harder to access. This process is apparently rewarding as it enables the exploration of yet undiscovered inner territories of the viewer’s brain.